Christmas in Camelot - Osborne, Mary Pope; Murdocca, Sal (New York : Random House, 2001)
On Christmas Eve, Jack and Annie's tree house transports them to King Arthur's castle at Camelot, where they undertake a quest to the castle of the Otherworld.
"A Merlin mission."
"A Stepping Stone book."
Keywords: Children's stories; Christmas stories